A prospective study of cervical lesions diagnosed by liquid based cytology in Western Rajasthan, India population - Bagga, Neha; Elhence, Poonam; Rao, Meenakshi; Nalwa, Aasma; Khera, Sudeep; Bharti, Jyotsna Naresh; Singh, Pratibha; Shekhar, Shashank (International Journal of Research in Medical Sciences, 2019)
Background: Carcinoma cervix is the second most common malignancy of women in India after breast cancer. The present study was conducted to determine the spectrum of cervical lesions by liquid-based cytology in Western Rajasthan population. Methods: It is a Prospective study on 1087 cervical samples carried over a period of 1 year. Cervical samples were taken and processed by SurePath™ LBC. Results: Of total 1087 cases 959 were negative for intraepithelial lesion or malignancy (88.22%). 88 cases (8.09%) were reported as unsatisfactory. Among the non- neoplastic cases- bacterial vaginosis was reported in 209 cases (21.8%), Candida in 77 cases (8.02%), both Candida and bacterial vaginosis in 12 cases (1.25%), reactive cellular changes in 193 cases (20.12%), and Trichomonas vaginalis in 01 case. Among pre-malignant and malignant lesions, 40 cases (4.17%) the distribution was as follows-atypical squamous cells of undetermined significance 16(1.67%), atypical squamous cell-cannot rule out high grade 08 cases (0.83%), Low grade squamous intraepithelial lesion 04 cases (0.42%), high grade squamous intraepithelial lesion 07 cases (0.73%), Atypical glandular cell favoring neoplastic 01 case (0.15%), and squamous cell carcinoma 04 cases (0.42%). Histopathological co-relation of premalignant and malignant lesions was further studied. Conclusions: Liquid based cytology is an effective screening and diagnostic procedure for cervical abnormalities. Among pre-malignant and malignant lesions, histo-pathological correlation increased with increased grade of severity of lesions. To the best of knowledge, this is the largest study of liquid based cytology in the Western Rajasthan.